Recrutamento do peixe-rei, Atherinella brasiliensis (Quoy & Gaimard) (Atheriniformes, Atherinopsidae), na margem continental da Baía de Sepetiba, Rio de Janeiro, Brasil - Pessanha,André Luiz Machado (2001)
The silverside, Atherinella brasiliensis (Quoy & Gaimard, 1824), a resident species of the shallows of bays, estuaries and coastal lagoons, was studied during two annual cycles, using beach seines (July 1996 to June 1998), in the continental margin of the Sepetiba Bay, aiming to assess recruitment and distribution patterns. A wide recruitment period, with young-of-the-year appearing from early spring to early autumn, was shown, with peaks of juveniles (Total Length-LT = 10-30 mm) being recorded in two periods of the year; one in November and another in March. The highest abundances, of both juvenile and adults, were recorded in Coroa Grande and Itacuruçá, sites located in the outer Bay, during the whole summer, with significant differences were found. In spite of not having been found any statistically significant relationship between the environmental factors and the occurrence of this species, a trend of higher abundance in colder and more saline waters was detected. High values of growth coefficient (K = 0.93) and low asymptotic lenght (L∞ = 11.6 cm) indicated that this species shows a high growth rate and short life cycle, with life span of 3.09 years, in this system.